2011
DOI: 10.1007/s12034-011-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of Ta 2 O 5 thin films prepared by photo-induced CVD

Abstract: Tantalum oxide (Ta 2 O 5 ) films and Al/Ta 2 O 5 /Si MOS capacitors were prepared at various powers by ultraviolet photo-inducing hot filament chemical vapour deposition (HFCVD). Effects of ultraviolet light powers on the structure and electrical properties of Ta 2 O 5 thin films were studied using X-ray diffraction (XRD) and atomic force microscopy (AFM). The dielectric constant, leakage current density and breakdown electric field of the samples were studied by the capacitance-voltage (C-V) and current-volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…37 As for TaBFA, there was evidence of a small quantity of other crystalline phases apart from little intense peaks, similar to those found for TaTTA, corresponding to orthorhombic Ta 2 O 5 (JCPDS 00-054-0514 and JCPDS 01-070-4775), and in addition we detected a large background between 15°and 40°in 2θ, which corresponds to the amorphous tantalum-based host. 38,39 Thermal treatment of the TaTTA complex (Fig. 8A) afforded a mixture of the same orthorhombic Ta 2 O 5 crystalline phases observed previously, even for the complex annealed at higher temperatures, but the phase percentages were different.…”
Section: Nanostructured Ta 2 Osupporting
confidence: 69%
“…37 As for TaBFA, there was evidence of a small quantity of other crystalline phases apart from little intense peaks, similar to those found for TaTTA, corresponding to orthorhombic Ta 2 O 5 (JCPDS 00-054-0514 and JCPDS 01-070-4775), and in addition we detected a large background between 15°and 40°in 2θ, which corresponds to the amorphous tantalum-based host. 38,39 Thermal treatment of the TaTTA complex (Fig. 8A) afforded a mixture of the same orthorhombic Ta 2 O 5 crystalline phases observed previously, even for the complex annealed at higher temperatures, but the phase percentages were different.…”
Section: Nanostructured Ta 2 Osupporting
confidence: 69%
“…For comparison, we measured the resistivity of traditional amorphous Ta 2 O 5 powders, which is more than an order of magnitude higher than that of the as-prepared a -Ta 2 O 5 (5.7 × 10 8 versus 4.2 × 10 7 Ω cm, as shown in Figure b). In addition, other studies even reported higher resistivity values from other forms of amorphous Ta 2 O 5 (>10 10 Ω cm). Therefore, the pressure-induced a -Ta 2 O 5 nanomaterial with improved electron transport ability appears to be a promising functional material in many energy-related applications, such as photovoltaic devices.…”
Section: Resultsmentioning
confidence: 99%
“…[111] This diffusion occurs primarily with alkali cations like sodium and potassium [112,113] that have a strong presence in biological fluids which are often a target of SiNW FET biosensors. Examples like Ta 2 O 5 , [116,117] TiO 2 , [118] or SrTIO 3 [119] are being implemented in nanoscale DRAMs, but are not fully compatible with SiNWs due to reaction either with Si (forming metallic silicides) or with water. [115] High-k dielectric layers offer a higher capacitance and better gate control, being less susceptible to these effects.…”
Section: Fabrication Of Sinw Devicesmentioning
confidence: 99%
“…High‐ k dielectric layers offer a higher capacitance and better gate control, being less susceptible to these effects. Examples like Ta 2 O 5 , TiO 2 , or SrTIO 3 are being implemented in nanoscale DRAMs, but are not fully compatible with SiNWs due to reaction either with Si (forming metallic silicides) or with water . Al 2 O 3 and HfO 2 are promising materials that can already be found in several examples of FETs, with an excellent pH sensitivity due to the high density of surface groups that buffer the pH changes of the solution .…”
Section: Fabrication Of Sinw Devicesmentioning
confidence: 99%